Hybrid task scheduling: integrating static and dynamic heuristics - Boeres, C.; Lima, A.; Rebello, V. E. F. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2003: Anais do XV Symposium on Computer Architecture and High Performance Computing, 2003)
Researchers are constantly looking for ways to improve the execution time of parallel applications on distributed systems. Although compile-time static scheduling heuristics employ complex mechanisms, the quality of their schedules are handicapped by estimated run-time costs. On the other hand, while dynamic schedulers use actual run-time costs, they have to be of low complexity in order to reduce the scheduling overhead. We investigate the viability of integrating these two approaches into a hybrid scheduling framework. The relationship between static schedulers, dynamic heuristics and scheduling events are examined. The results show that a hybrid scheduler can indeed improve the schedules produced by good traditional static list scheduling algorithms.